1188. Efficacy of Copper Impregnated Self-Sanitizing Surface Against Clostridioides difficile Spores. (15th December 2022) - Ashby, Landon; Navarathna, Thanuri; Coppin, John David; Chatterjee, Piyali; Williams, Marjory D; Bennett, Morgan; Choi, Hosoon; Hwang, Munok; Xu, Jing; Nelson, Richard; Allton, Yonhui; Jinadatha, Chetan
Abstract: Background: Clostridioides difficile ( C. diff ) is one of the most common causes of healthcare-associated infections (HAIs), leading to increased hospital stay, cost, and mortality. Elimination of C. diff spores is difficult as they are resistant to kill by common hospital grade disinfectants. Copper impregnated self-sanitizing surfaces (SSSCu) provide continuous reduction of vegetative pathogens, potentially lowering the risk of infections, but their efficacy on C. diff spores has not been previously evaluated. Methods: Control (no copper) and copper coupons containing 20% copper-oxide were inoculated with varying C. diff spore loads ranging from 10 5 to 10 7 spores, prepared using environmental protection agency protocol, with or without 5% fetal bovine serum (FBS) soil load. After 4 hours of contact time, the C. diff spores were recovered and tested for viability. The efficacy of copper (log10 kill) was estimated using a Bayesian linear multilevel model. Results: After 4 hours, the copper coupons, at mean initial spore load (6.67 log10 ) and no soil load, had a mean 1.21 (95% uncertainty interval: 1.13 - 1.31) log10 reduction compared to control coupons. With soil load, the treatment effect of copper decreased by 0.50 (95% uncertainty interval: 0.37 - 0.64) log10 . Also, for each additional standard deviation (SD) increase in initial spore load there was a 0.59 (95% uncertainty interval: 0.47 - 0.72) log10 decrease in the treatment effect of copper. The soil load in combination with increasing initial spore load further decreased the treatment effect of copper by an additional 0.19 (95% uncertainty interval: 0.01 - 0.38) log10 for each SD increase in initial spore load. Conclusion: Copper coupons can substantially reduce C. diff spores after 4 hours by 50%-97% depending on the initial spore concentration and presence or absence of organic material. Higher initial spore loads or excess organic material may prevent the spores from coming in contact with the copper-impregnated surface thus decreasing the kill efficacy. Continuous sporicidal effect of copper-impregnated surfaces might prevent transmission of spores and help reduce HAIs. Further studies are needed to evaluate the efficacy on C. diff HAI rates. Disclosures: Piyali Chatterjee, PhD, AHRQ Grant # 1R03HS027667-01: Grant/Research Support|AHRQ Grant # 1R03HS027667-01: Central Texas Veterans Health Care System Chetan Jinadatha, MD, MPH, AHRQ R01 Grant-5R01HS025598: Grant/Research Support|EOS Surfaces: Copper Coupons and materials for testing.